A READABILITY COMPARISON OF ONLINE SPANISH AND ENGLISH PATIENT EDUCATION MATERIALS ABOUT VISION HEALTH. (4th March 2022) - Karthik, Naveen; Barekatain, Kayvan; Vu, Hoang; Wu, Danny T.Y.; Ehrlich, Joshua R.
ABSTRACT: Purpose: Current United States national guidelines recommend patient education materials (PEMs) be written at a 5 th –6 th grade level. The objective of this study was to compare the readability of Spanish vision and eye health PEMs to nationally recommended reading levels and to English versions of the same PEMs. Methods: PEMs were collected from seven online websites of vision-related organizations that provided PEMs with Spanish and English versions. PEMs were downloaded for text to be extracted and analyzed. Readability scoring was performed with Índice Flesch-Szigriszt, Spanish and English Lexile Text Analyzers, and Flesch–Kincaid Grade Level. Results: A total of 484 PEMs with Spanish and English versions were analyzed. Readability for Spanish PEMs was reported at or above the 6 th grade level for 57% of articles based on Spanish Lexile scoring and 63% based on Índice Flesch-Szigriszt scoring. Readability for English PEMs was reported at or above the 6 th grade level for 66% of articles based on English Lexile scoring and 75% based on Flesch–Kincaid Grade Level scoring. Wilcoxon signed–rank test comparing grade levels translated from Lexile scores for Spanish and English versions of PEMs revealed that Spanish versions of PEMs required higher grade reading levels compared to English versions of PEMs ( p < .001). Conclusion: Spanish and English PEMs were written above nationally recommended reading levels. Online sources providing multilingual vision and eye health education should consider routinely monitoring PEMs to ensure reading levels meet the literacy needs of their audiences.